Cuidados paliativos pediátricos: Arte, essência e ciência no cuidado de crianças com doenças limitantes ou ameaçadoras da vida - Santos, Gabriella Cézar dos (2017)
Pediatric palliative care is a health care approach, based on humanitarian and scientific principles, which proposes broad, multidisciplinary and active assistance in promoting quality of life, minimizing the pain and suffering of children with life-limiting or life-threatening diseases. The philosophy of palliative care benefits integral care, from the diagnosis on. It values the biological, psychological, social, and spiritual aspects, respecting life and death as natural processes, seeking to preserve the maximum of autonomy and dignity. This study aimed to understand the concepts and practices of health professionals working in Pediatric Intensive Care Units (PICUs) on pediatric palliative care and dignified death. It was a cross- sectional, descriptive, and analytical study, with a quantitative qualitative approach. The field of investigation was the PICUs of three hospital institutions in the city of Campina Grande, in the state of Paraíba. Thirty health professionals from the staff of the PICUs participated in this study. The professionals were contacted by the criterion of accessibility and the total of participants was defined by the criterion of saturation. The instruments of data collection were a social demographic questionnaire to delineate the profile of the professionals, and a semi- structured interview with questions about the humanization of the care, about the concepts and practices of pediatric palliative care in PICUs, about the assistance provided for children with life-limiting or life-threatening conditions and in a reserved prognosis situation, about how professionals deal with the death of children in PICUs and about the possibility of a dignified death for children in hospital care. The social demographic data were evaluated through descriptive statistics and the interviews were analyzed through content analysis and the technique of enunciation analysis. To give better visibility to the results, we used the resource of sense association trees. The results were coupled into two categories: Concepts, practices, feasibility and limits of pediatric palliative care in PICUs; and Dealing with death in PICUs. Results showed that knowledge about the purposes, the comprehensiveness of the palliative approach, and the possibilities of action of the intensive staff in this field of care are insufficient. Some professionals know some of the principles and identify the demand. However, they stumble on institutional and cultural issues that make the dialogue and the accomplishment of pediatric palliative care difficult. Dying in the PICUs is preceded, for the most part, by measures that try to prolong the death process as much as possible. Dealing with death and the suffering of children are situations described as difficult. Most of the participants understand the pillars that give sustainability to the concept of a dignified death, although others are totally unaware of this. We expect that this study will contribute to the advancement of scientific literature on the Brazilian reality regarding palliative care and the humanization of death in the pediatric context. This research can stimulate reflections, enhance discussions, and contribute to the empowerment of health professionals and the society in general in the humanization of health care.